Normal insulin sensitivity, glucose tolerance, gut incretin and pancreatic hormone responses in adults with atopic dermatitis. Issue 11 (19th August 2020) - Gether, Lise; Thyssen, Jacob P.; Gyldenløve, Mette; Hartmann, Bolette; Holst, Jens J.; Foghsgaard, Signe; Vilsbøll, Tina; Knop, Filip K.
Abstract: Aim: To examine whether adults with mild to moderate atopic dermatitis (AD) had reduced insulin sensitivity and/or exhibited other gluco‐metabolic disturbances compared with carefully matched healthy controls. Materials and methods: Sixteen adult, non‐obese, non‐diabetic patients with mild to moderate AD and 16 gender‐, age‐ and body mass index (BMI)‐matched healthy controls underwent a hyperinsulinaemic euglycaemic clamp (insulin infusion rate: 40 mU/m 2 /minute) and an oral glucose tolerance test (OGTT) with frequent blood sampling for gut and pancreatic hormones. Results: The two groups were similar in age (33 ± 3 vs. 33 ± 3 years, mean ± standard error of the mean [SEM]), gender (56% women), BMI (24.5 ± 0.7 vs. 24.4 ± 0.7 kg/m 2 ), physical activity level, fasting plasma glucose and HbA1c. Patients with AD had a mean Eczema Area and Severity Index score of 8.5 ± 1.0 (moderate disease) and a mean AD duration of 28 ± 3 years. During the OGTT, circulating glucose, insulin, C‐peptide, glucagon and glucose‐dependent insulinotropic polypeptide, respectively, were similar in the two groups, except glucagon‐like peptide‐1, which was higher in patients with AD. The clamp showed no differences in insulin sensitivity between groups (M‐value 9.2 ± 0.6 vs. 9.8 ± 0.8, P = .541, 95% CI −1.51; 2.60), or circulating insulin, C‐peptide and glucagon levels. Conclusions: Using OGTT and the hyperinsulinaemic euglycaemic clamp technique, we found no difference in insulin sensitivity or other gluco‐metabolic characteristics between patients with mild to moderate AD and matched healthy controls, suggesting that the inflammatory skin disease AD has little or no influence on glucose metabolism.